Inoculant of Arbuscular Mycorrhizal Fungi (Rhizophagus clarus) Increase Yield of Soybean and Cotton under Field Conditions - Cely, Martha V. T.; de Oliveira, Admilton G.; de Freitas, Vanessa F.; de Luca, Marcelo B.; Barazetti, André R.; dos Santos, Igor M. O.; Gionco, Barbara; Garcia, Guilherme V.; Prete, Cássio E. C.; Andrade, Galdino (Frontiers in Microbiology, 2016)
Nutrient availability is an important factor in crop production, and regular addition of chemical fertilizers is the most common practice to improve yield in agrosystems for intensive crop production. The use of some groups of microorganisms that have specific activity providing nutrients to plants is a good alternative, and arbuscular mycorrhizal fungi (AMF) enhance plant nutrition by providing especially phosphorus (P), improving plant growth and increasing crop production. Unfortunately, the use of AMF as an inoculant on a large scale is not yet widely used, because of several limitations in obtaining a large amount of inoculum due to several factors, such as low growth, the few species domesticated under in vitro conditions, and high competition with native AMF. The objective of this work was to test the infectivity of a Rhizophagus clarus inoculum and its effectiveness as an alternative for P supply in soybean (Glycine max L.) and cotton (Gossypium hirsutum L.). The experiments were carried out in plots and the treatments were: Fertilizer; AMF, AMF + Fertilizer and AMF + ½ Fertilizer; non-inoculated and non-fertilized plants were considered the control. The parameters evaluated were AMF root colonization and effect of inoculation on plant growth and yield under a field conditions. The results showed that AMF inoculation increased the effect of fertilizer application in soybean, and that in cotton R. clarus was more effective than chemical fertilizer